Greater BOLD response to working memory in endurance‐trained adults revealed by breath‐hold calibration - Gonzales, Mitzi M. (Hum Brain Mapp, 2013)
BACKGROUND: Cardiorespiratory fitness is associated with increased frontal and parietal activation during executive function tasks. While these findings suggest fitness‐related enhancement of neuronal response, the utility of functional magnetic resonance imaging (fMRI) may be limited by potential fitness‐related differences in global vascular reactivity. The aim of this study was to determine if highly fit adults display differential activation during working memory after calibration for vascular reactivity relative to their sedentary counterparts. METHODS: Thirty‐two endurance‐trained and 24 sedentary adults, aged 40–65 years, completed a 2‐Back verbal working memory task and a breath‐hold challenge during fMRI. Group differences in blood oxygen level‐dependent (BOLD) response during working memory were examined across the whole brain and in a priori regions of interest (ROI) before and after breath‐hold calibration using non‐parametric permutation testing. Multiple regression was used to explore the association between cardiorespiratory fitness (VO(2)max), age, and calibrated 2‐Back‐related activation within the one a priori ROI with significant group effects. RESULTS: In comparison to the endurance‐trained group, the sedentary group exhibited greater BOLD signal changes in response to the breath‐hold task. After, but not before calibration, the endurance‐trained group displayed significantly higher 2‐Back‐related activation in the right middle frontal gyrus (P = 0.049). Older age predicted lower 2‐Back‐related activation (ß = −0.308, P = 0.031), whereas fitness predicted higher activation (ß = 0.372, P = 0.021) in this region. CONCLUSIONS: Breath‐hold calibration increased detection of working memory‐related BOLD response differences between sedentary and endurance‐trained adults. Moreover, cardiorespiratory fitness appeared to mitigate age‐related changes in BOLD during working memory in this region. Hum Brain Mapp 35:2898–2910, 2014. © 2013 Wiley Periodicals, Inc.